2021
DOI: 10.3390/buildings11100456
|View full text |Cite
|
Sign up to set email alerts
|

Framing and Evaluating the Best Practices of IFC-Based Automated Rule Checking: A Case Study

Abstract: This research reviews recent advances in the domain of Automated Rule Checking (ARC) and argues that current systems are predominantly designed to validate models in post-design stages, useful for applications such as e-permitting. However, such a design-check-separated paradigm imposes a burden on designers as they need to iteratively fix the fail-to-pass issues. Accordingly, the study reviews the best-practices of IFC-based ARC systems and proposes a framework for ARC system development, aiming to achieve pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Since the system is still in the research team's internal usage stage, it has not been extensively utilized, so we do not have enough data to conduct a study on how user-friendly the system is and how long the investment return time is. By collaborating closely with end-users, proactive systems could be developed [36]. Ideally, we would conduct surveys to determine the effectiveness and usability of the current system, and a focus group that uses the system and reports feedback would be required to help evaluate the system.…”
Section: Limitationsmentioning
confidence: 99%
“…Since the system is still in the research team's internal usage stage, it has not been extensively utilized, so we do not have enough data to conduct a study on how user-friendly the system is and how long the investment return time is. By collaborating closely with end-users, proactive systems could be developed [36]. Ideally, we would conduct surveys to determine the effectiveness and usability of the current system, and a focus group that uses the system and reports feedback would be required to help evaluate the system.…”
Section: Limitationsmentioning
confidence: 99%
“…Over 400 software applications, including Solibri [2], Revit [3], Bentley [4], and SketchUp [5], enable the exchange of IFC data among stakeholders. Many studies have shown that IFC data can be exchanged and managed for rule checking [6] and structural design analysis [7] during the design phase, construction cost estimation [8] and progress monitoring [9] during the construction phase, and structural health monitoring [10] during the operation and maintenance (O&M) phase. In short, IFC enables the exchange of information between BIM and other IFC-compatible environments, which improves the efficiency, effectiveness, and performance of whole lifecycle management.…”
Section: Introductionmentioning
confidence: 99%
“…Level 3A is often achieved by project enterprises, general contractors, or consortia of companies. Nevertheless, despite various ontology-level solutions, designers are still often forced to iteratively fix interoperability failures [19]. Level 3B is a similar challenge.…”
Section: Introductionmentioning
confidence: 99%